Spirituality and religious coping in African-American youth with depressive illness - Breland-Noble, Alfiee M. (Mental health, religion & culture, 2015)
The research team completed a secondary data analysis of primary data from a 2-phase depression treatment engagement behavioural trial to assess African-American adolescents’ reported experiences of spiritual and religious coping when dealing with depression. The team utilised data collected from 28 youth who participated in focus groups or individual interviews. Qualitative data were analysed using thematic techniques for transcript-based analysis to identify the key patterns and elements of the study participants’ accounts and to extract six primary themes. The main themes are reported in this manuscript and include; "Religion as Treatment Incentive", "Prayer & Agency", "Mixed Emotions", "Doesn't Hurt, Might Help", "Finding Support in the Church", and "Prayer and Church: Barriers to Treatment?" Overall, the data suggested that religion and spirituality play a key role in African-American adolescents’ experiences of depression. As well, it is surmised that these factors may be important for improving treatment-seeking behaviours and reducing racial mental health disparities in this population of youth.